Analisis Pengguna Tenant Terhadap Pemakaian Aplikasi Fintech Dana Di OPI Mall Palembang Dengan UTAUT 2 - Akbar, Doni; Abdillah, Leon A. (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Advances in information technology have significantly impacted various aspects of life, including the payment sector. Innovations such as digital payments and e-wallets have transformed the way financial transactions are conducted. In Indonesia, the fintech sector is rapidly growing, with payment applications like DANA being one of the contributors. However, at OPI Mall Palembang, there is a gap between expectations and reality in the use of the DANA fintech application by tenant users. Although users hold a positive view of the application, cash usage still dominates. This research aims to analyze the level of tenant user acceptance of the DANA fintech application at OPI Mall Palembang using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) framework. Through this study, it is expected that the causes of low utilization of the DANA fintech application can be understood, and solutions and recommendations to enhance its usage in the future can be provided. A deeper understanding of the acceptance and usage levels of this application is expected to result in strategic steps to increase user awareness, comfort, and confidence in using the DANA fintech application.